Avaliação da qualidade dos habitats da Mata do Cipó e das nascentes do riacho Siriri - Capela, SE - Battesini, Marcela Dórea (2014)
In the present study, we applied a fast diagnostic protocol to the analysis of the quality of aquatic habitats (PAR) to assess the headwaters of the Siriri River, a first-order tributary of the Japaratuba River basin, Sergipe. The main source is located at UTM (707680, 8837848) in a 100-hectare fragment of Atlantic Forest, in the coastal plateau domain. The diagnosis proposed to evaluate external and internal human pressures, impacts resulting from the use of land and the exploitation of forest resources by the local Mata do Cipó community. The environmental diagnosis of this community was based on 52 semi-structured questionnaires applied to 24 men and 28 women, used to identify local conflicts, and the use of land and water resources. Land use was characterized by an historical overview together with a description of the geomorphology and aspects of the geology, soil, topography, climate, and vegetation. The rapid assessment protocol of habitat quality (RAP), adapted from Callisto et al (2002) was applied at 13 points along the Siriri stream, where a series of physical-chemical parameters of the water (pH, DO, TDS, ORP, eH, salinity, and total N and P) were analyzed and compared with the water quality parameters recommended by CONAMA (357). The environmental diagnosis of the community indicated a strong historical dependence for more than 80 years, the intensive exploitation of forest resources for bathing, hunting, leisure activities, and religious practices (African beliefs). The principal external pressure was the use of the land for sugarcane plantations and the main internal pressure was the exploitation of water resources by the neighboring town of Capela. The RAP concluded that 25% of the aquatic habitats are altered, with a loss of environmental resistance, while pH, nitrogen, and eH all exceeded CONAMA recommendations. We conclude that (a) this fragment of Atlantic Forest is a conservation priority due to the confirmation interviewees of the local occurrence and extinction of the titi monkey, Callicebus coimbrai Kobayashi & Langguth, 1999), (b) despite a low level of impact (25%) on this headwater environment, some physical-chemical parameters of the water have been affected, and (c) the local ecosystem appears to be resilient, although the habitats that surround the headwaters of the Siriri River require restoration.